Staphylococcus aureus bloodstream infections in Latin America: results of a multinational prospective cohort study (2017)
Background:Substantial heterogeneity in the epidemiology and management ofStaphylococcus aureusbacter-aemia (SAB) occurs in Latin America. We conducted a prospective cohort study in 24 hospitals from nine LatinAmerican countries.Objectives:To assess the clinical impact of SAB in Latin America.Patients and methods:We evaluated differences in the 30 day attributable mortality among patients with SABdue to MRSA compared with MSSA involving 84 days of follow-up. Adjusted relative risks were calculated using ageneralized linear model.Results:A total of 1030 patients were included. MRSA accounted for 44.7% of cases with a heterogeneous geo-graphical distribution. MRSA infection was associated with higher 30 day attributable mortality [25% (78 of 312)versus 13.2% (48 of 363), adjusted RR: 1.94, 95% CI: 1.38–2.73,P,0.001] compared with MSSA in the multivari-able analysis based on investigators’ assessment, but not in a per-protocol analysis [13% (35 of 270) versus8.1% (28 of 347), adjusted RR: 1.10, 95% CI: 0.75–1.60,P"0.616] or in a sensitivity analysis using 30 day all-cause mortality [36% (132 of 367) versus 27.8% (123 of 442), adjusted RR: 1.09, 95% CI: 0.96–1.23,P"0.179].MRSA infection was not associated with increased length of hospital stay. Only 49% of MSSA bloodstream infec-tions (BSI) received treatment withb-lactams, but appropriate definitive treatment was not associated withlower mortality (adjusted RR: 0.93, 95% CI: 0.70–1.23,P"0.602).Conclusions:MRSA-BSIs in Latin America are not associated with higher 30 day mortality or longer length ofstay compared with MSSA. Management of MSSA-BSIs was not optimal, but appropriate definitive therapy didnot appear to influence mortality